The Relationship of Family Communication Level With The Sexual Behavior of Adolescent With Disability In The Umbrella Disability Project (UDP) Bukittinggi City - Liza Andriani; Chyka Febria; Resi Oktavia (Universitas Andalas, 2021)
According to Survey Demografi Kesehatan Indonesia (SDKI) at 2018, it is said that adolescents who have knowledge about reproductive health are still lacking with a percentage of 35.3% of female adolescents and 31.2% of male adolescents aged 12-19 years. Individuals have reached a developmental transition that is closer to adulthood. This growth and development is not only experienced by normal adolescents but also experienced by adolescents with disabilities. The purpose of this study was to determine the relationship between the level of family communication and adolescent sexual behavior in the UDP community in Bukittinggi City. This type of research is descriptive analytic with a cross sectional design. The population of this study were all youth with disabilities (deaf) who were in the Umbrella Disability Project (UDP) community as many as 30 respondents. The sampling technique was carried out by total sampling. The results of this study were almost half (43.3%) of respondents had poor family communication levels and less than half (33.3%) of respondents had poor sexual behavior. After carrying out the Chi-square analysis test, it was found that there was a significant relationship between the level of family communication and the sexual behavior of adolescents with disabilities in the UDP community in Bukittinggi City (p < 0.05). Based on this research, it is concluded that adolescents with disabilities during their growth and development need special attention, especially parents and families to prevent risky sexual behavior so that it is not difficult for them to discuss efforts to prevent negative sexual behavior in society